Education and modernity - Dennis O'Keeffe (Institute of Economic Affairs (IEA), 2002)
I want to say something tonight about modernity and in particular modernity's very problematic connections with our educational arrangements. I have accordingly entitled my paper EDUCATION AND MODERNITY. I feel bound to touch also on the strange conceit that modernity has now past and that we are in a condition of "Post-Modernity." My main concern, however, will be with a particular economic sociology of education which I hope will both explain some of our educational shortcomings and point the way to eliminating them. My central positive claim is the unoriginal one that modernity is a mix of private enterprise and legally constituted representative government. I will spell out the key sociological features of this mix as well as its economic details. My central critical claim is that our education system has a paradoxically perverse relationship to the modern order. On the one hand, without mass education there could be no modernity. On the other hand, the economic arrangements of education do not themselves conform to modernity. When we look at contemporary educational organisation, we find some of the features of the very modernity it helps to secure, egregiously missing. Before I enlarge on today's educational shortcomings, however, I will have to plunge briefly into the problematic quagmire of "modernity." I will say what the socalled "Post-Modernists" seem to me to be saying and also I will dwell a little on how conservative views on modernity differ from libertarian ones. I understand "conservative" to mean "wishing to maintain our traditional civilisation." I understand "libertarian" to mean "wishing to free us from unnecessary laws and regulations and restrictions." There is no necessary tension between these positions. Lots of people are conservative and libertarian. I am for example. The reason a brief digression on conservatism and libertarianism is relevant to my thesis is easy to explain. Conservatives and libertarians would virtually all take varying degrees of offence at our educational arrangements. Socialists on the other hand will support them overwhelmingly.
Keywords: 330; Education; Educational research; Pedagogy; Great Britain; Bildungswesen; Bildungsforschung; Pädagogik; Großbritannien